Stable isotope measurements to differentiate sources of monofluoroacetate in a blackmail case. (12th April 2019) - Van Hale, Robert; Schofield, Matthew; Connor, Mark; Barker, Richard; Frew, Russell
Abstract : Rationale: Stable isotope ratios can provide a 'fingerprint' to enable differentiation of sources of monofluoroacetate (MFA), hence providing a means to eliminate potential sources of MFA in a blackmail case involving the contamination of milk. Methods: The stable isotopic compositions ( δ 2 H, δ 13 C and δ 18 O values) of a library of 43 samples of MFA were determined and multivariate models constructed to differentiate samples of different composition. The data from the MFA library were compared with those obtained from MFA extracted from contaminated milk powder (the case samples). The isotopic composition of the extracted samples was measured on dichloroaniline derivatives. Results: A wide range of values was found for δ 2 H, δ 13 C and δ 18 O of the MFA samples, much greater than the analytical repeatability between subsamples. Stable isotope data, therefore, provide a means of distinguishing samples of MFA. Of the 43 MFA samples tested, all but 6 could be eliminated as potential sources of the contamination, i.e. they had a distinctly different isotopic composition such that they must have had different histories and/or origins. Conclusions: Stable isotope measurements of bulk and derivatized MFA provide an effective means of discriminating MFA samples. Three of the library samples that could not be differentiated from the case samples were directly connected to the suspect, and this evidence contributed to the suspect's admission of guilt.